PENGARUH PENGGUNAAN PGPR (PLANT GROWTH PROMOTING RHIZOBACTERIA) TERHADAP INTENSITAS TMV (TOBACCO MOSAIC VIRUS), PERTUMBUHAN, DAN PRODUKSI PADA TANAMAN CABAI RAWIT (Capsicum frutescens L.) - Kamila Qurota A’yun; Tutung Hadiastono; Mintarto Martosudiro (Jurnal HPT (Hama Penyakit Tumbuhan), 2013)
One of the main disease of chili cultivation is mosaic disease that is caused by TMV (Tobacco Mosaic Virus). One effort to control the disease could be done by applying Plant Growth Promoting Rhizobacteria (PGPR). PGPR is a useful bacteria that lives and grows well in soil that contain much of organic matter. This research aimed to determine the effect of application and the role of PGPR Pseudomonas fluorescens, Azotobacter sp., dan Bacillus subtilis on TMV attack intensity, the height and production of chili plant. This research was conducted in screen house and plant disease laboratory, Brawijaya University Malang. The experiment started in April until August 2012. This research was using complete randomized design. The treatments used one species of PGPR bacteria and the combination of two species of PGPR bacteria. The PGPR were PGPR P. fluorescens, PGPR Azotobacter sp., or PGPR B. subtilis. Whereas the PGPR combination were PGPR P. fluorescens and PGPR Azotobacter sp., PGPR P. fluorescens and PGPR B. subtilis, or PGPR Azotobacter sp. and PGPR B. subtilis. Control were executed without applying PGPR. Results showed that the combination of P. fluorescens and Azotobacter sp. PGPR affected on reducing the incubation periode, the attack intensity of TMV, and increasing the plant height. The incubation periode for chili plants with PGPR P. fluorescens and Azotobacter sp. was 16,67 days. The PGPR P. fluorescens and Azotobacter sp. reduced TMV attack intensity on chili plants until 89,92%. The plant height of chili plants with PGPR P. fluorescens and Azotobacter sp. could reach 69,25 cm. PGPR P. fluorescens dan B. subtilis treatment could increase the average fruit weight of chili until 2,17 grams per plant.